Growth Behaviour of Poplar (Populus deltoides) Clones under Farm Forestry - Verma, Archana; Saralch, H. S.; Chauhan, Sanjeev; Saresh, N.V.; Sankanur, M.; Srivastva, Varun (Indian Forester, 2013)
The study was conducted to explore the growth performance of different clones of Populus deltoides under farm forestry. The experiment was established during February, 2006 with six poplar clones under two environments i.e. pure poplar plantation and agroforestry plantation (poplar with wheat and mung) and laid out in Split Plot Design with three replications. Results of the studies revealed that all growth parameters of poplar clones i.e. DBH, height and crown spread exhibited better performance under agroforestry plantation. Overall, clone SWL 22 showed best performance under both the environments.